Combined powder X-ray diffraction data and quantum-chemical calculations in EXPO2014. (21st February 2017) - Altomare, Angela; Ciriaco, Fulvio; Cuocci, Corrado; Falcicchio, Aurelia; Fanelli, Flavio
Abstract : This paper describes new features implemented in the EXPO2014 software and aimed at assisting crystallographers in the use of quantum-chemistry calculations in combination with experimental powder diffraction data. The implemented tools are useful in particular in two important steps of the process of crystal structure determination from powder diffraction data: (1) preparing accurate structural model suitable for crystal structure determination by real-space methods; (2) validating structure determination. The combination of experimental/quantum-chemical methods in EXPO2014 is now managed easily thanks to the following capabilities: (a) converting crystallographic data in input files and reading molecular geometry from output files of a wide variety of computational chemistry packages (GAMESS-US, NWChem, Gaussian, CRYSTAL, ABINIT, QUANTUM ESPRESSO); (b) optimizing the geometry of a molecule using Open Babel's force fields; (c) a graphical interface to run semi-empirical quantum calculation by MOPAC (Molecular Orbital PACkage); (d) producing input file for dispersion-corrected density functional theory.